A new modification of the dental prosthesis in the postoperative restoration of chewing function - Kirill Ershov, Andrey Sevbitov, Nikolay Mitin, Maria Kuznetsova, Maria Kuznetsova, (Opción, 2020)
The purpose of this study is clinical testing of the effectiveness of the influence of the treatment methods on the masticatory function of dental patients. As a result, by the 30th day of postoperative aftertreatment, the level of function of mastication in the main group significantly and authentically (р ≤ 0,05) exceeded a similar indicator in the control group. In conclusion, use or modification of tooth and dentoalveolar prostheses with punctual retentions on a basic basis in combination with the use of Visposil phytoointment leads to faster and high-quality optimization of chewing function during postoperative aftertreatment at stomatologic patients.